Analisis Tarif Ideal Angkutan Barang Lintas Banjarmasin – Amuntai: Ideal Rate Analysis Of Crossing Goods Transport Banjarmasin – Amuntai - Hudan Rahmani; Aminullah Aminullah; Noor Jasmani; Nova Abriano; Hendra Cahyadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Tariff is the level of price or fee paid by users of goods transport services per unit trip, weight or per unit volume per kilometer. Because the tariff is intended to encourage the creation of optimum use of transportation infrastructure and facilities by considering the traffic concerned. In calculating the cost (transportation rate) of goods using an approach to vehicle production costs, it means that the ideal freight rate is determined based on vehicle operating costs plus a number of percentages of management and profits that are allowed. This case study reviews the special freight rates for the Banjarmasin – Amuntai route along 200 km. by land transportation. Where in this case, due to low tariffs, the tendency of owners of transportation services to increase the number of transport loads, one of the impacts on road network infrastructure is not achieving the planned age of the road construction. The calculation of transportation rates refers to the technical guidelines for determining tariffs for goods and passengers from the Director General of Land Transportation of the Ministry of Transportation with three basic components, namely ownership costs, fixed costs and vehicle operating costs. From the combination of the three components, the basic tariff value for goods transportation from Banjarmasin - Amuntai per kilogram is Rp.681.39 so that the expedition company can determine the ideal tariff according to the level of service to service users